Spatial trends of trace elements bioaccumulation in the most endangered dolphin from the Southwestern Atlantic Ocean: The franciscana (Pontoporia blainvillei) - Vannuci-Silva, M.; Manhães, B. M.R.; Guari, E. B.; Botta, S.; Colosio, A. C.; Barbosa, L. A.; Bertozzi, C. P. [UNESP]; Azevedo, A. F.; Cunha, H. A.; Bisi, T. L.; Lailson-Brito, J. (Elsevier, 2022)
Trace elements bioaccumulation patterns can be an important tool to assess differences among cetaceans' populations. In this work, their use as potential chemical markers to differentiate franciscanas (Pontoporia blainvillei) populations was evaluated. Franciscanas were collected from three states in southeastern Brazil, which comprise three different Franciscana Management Areas (FMAs): Espírito Santo (FMA Ia), southern Rio de Janeiro (FMA IIa), and central São Paulo (FMA IIb). The concentrations of As, Cd, Cu, Fe, Hg, Mn and Zn were determined in the muscle, liver and kidney of the animals. Cadmium was the most valuable chemical marker to differentiate stocks, separating at least FMA IIa from the others. The higher Cd levels in FMA IIa, along with dietary information, indicate that the predominant consumption of cephalopods by this population is the main reason for the differences found. Additionally, environmental characteristics of the areas should also be considered as divergent sources of trace elements. Our findings suggest that non-essential trace elements, such as Cd, can be successful markers to differentiate populations. The Mn concentrations in FMA Ia raised concern and must be carefully monitored, as well as other elements that compose the iron ore tailings that have impacted the Espírito Santo coastal area. Additionally, this is the first study to report trace element concentration in the franciscanas from FMA IIa (southern Rio de Janeiro). Trace element concentrations found in franciscanas may represent different contamination levels in their preys and environments, which might pose specific threats to distinct populations. Therefore, our findings are important to characterize and differentiate franciscana populations and to guide precise management and conservation actions for the distinct stocks of this endangered species.
Keywords: Cetaceans; Chemical markers; Contaminants; Geographical groups; Metals; Stocks